2022
DOI: 10.1186/s12864-022-08333-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic architecture of phenotypic extremes in a wild cervid

Abstract: Identifying the genes underlying fitness-related traits such as body size and male ornamentation can provide tools for conservation and management and are often subject to various selective pressures. Here we performed high-depth whole genome re-sequencing of pools of individuals representing the phenotypic extremes for antler and body size in white-tailed deer (Odocoileus virginianus). Samples were selected from a tissue repository containing phenotypic data for 4,466 male white-tailed deer from Anticosti Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“…Here, insular masked shrews exhibited different phenotypes than their mainland counterparts; morphologically, this presented as decreased body length, mass, and skull length on islands. Body size is a polygenic trait (Posbergh & Huson, 2021) with many underlying mechanisms, often making it difficult to clearly understand the role of each gene or pathway involved (e.g., Anderson et al, 2022). DNA methylation has been suggested as a universal mechanism that regulates body mass and morphological development in animals (Cao et al, 2015; Haghani et al, 2021), and appears to help regulate intra-species differences in island-mainland settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, insular masked shrews exhibited different phenotypes than their mainland counterparts; morphologically, this presented as decreased body length, mass, and skull length on islands. Body size is a polygenic trait (Posbergh & Huson, 2021) with many underlying mechanisms, often making it difficult to clearly understand the role of each gene or pathway involved (e.g., Anderson et al, 2022). DNA methylation has been suggested as a universal mechanism that regulates body mass and morphological development in animals (Cao et al, 2015; Haghani et al, 2021), and appears to help regulate intra-species differences in island-mainland settings.…”
Section: Discussionmentioning
confidence: 99%
“…Here, insular masked shrews exhibited different phenotypes than their mainland counterparts; morphologically, this presented as decreased body length, mass, and skull length on islands. Body size is a heritable polygenic trait in mammals (Posbergh & Huson, 2021;Postma, 2014) with many underlying mechanisms, often making it difficult to clearly understand the role of each gene or pathway involved (e.g., Anderson et al, 2022). Cytosine methylation levels measured in highly conserved stretches of DNA have been linked to mammalian traits such as maximum lifespan (Haghani et al, 2021) and has been suggested as a universal mechanism to regulates body mass and morphological development in animals in other association studies (Cao et al, 2015;Haghani et al, 2021).…”
Section: Phenotypic and Epigenetic Divergencementioning
confidence: 99%
“…Mule deer and white-tailed deer can hybridize (Stubblefield, Warren, & Murphy, 1986), so we opted to use the long-read-based draft genome of white-tailed deer ( Odocoileus virginianus ) (Accession No. JAAVWD000000000) that was recently annotated (Anderson, Côté, Richard, & Shafer, 2022); we note that the available mule deer genome is simply a consensus sequence from reads mapped to earlier versions of the white-tailed reference (Russell et al, 2019). We performed initial quality filtering for all reads using fastqc and trimmed reads for quality and adaptors using the default Trimmomatic v.0.36 settings (Bolger et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…We used the program Gowinda v1.12 (Kofler & Schlötterer, 2012) to determine GO term enrichment while accounting for gene length biases. We created a .gtf version of our annotation by removing duplicated genes, retaining only the longest version of each gene, which resulted in 15,395 unique genes in the annotation (Anderson et al, 2022). All outlier SNPs that SnpEff identified as being on or within 25kbp of genic regions were used to analyze gene ontology and compared to all outlier SNPs in every qualifying window.…”
Section: Methodsmentioning
confidence: 99%
“…We used the program Gowinda v. 1.12 [65] to determine GO term enrichment while accounting for gene length biases. We created a .gtf version of our annotation by removing duplicated genes, retaining only the longest version of each gene, which resulted in 15 395 unique genes in the annotation [49]. All outlier SNPs that SnpEff identified as being on or within 25 kbp of genic regions were used to analyze gene ontology and compared to all outlier SNPs in every qualifying window.…”
Section: (E) Gene Ontologymentioning
confidence: 99%